Une masculinité en crise à la fin du XVIIe siècle ? La critique de l'efféminé chez La Bruyère - Cédric Corgnet (Genre & Histoire)
The effeminate is always a sexual limit case: man in the feminine sights, he questions the innate of the sexual nature, criticizes genders and their explicitly physical definition. The end of the XVIIth century illustrates this tension at the French moralists and especially in La Bruyère’s Characters where this one questions this generic monstrousness through a semiological analysis. But this teratology is not above all clinical but social and moral: he warns us, by this distance from gender, from a moral corruption of the world both by a clinical semiology and ovidian mythology not looking for the pathological realism but the antic filiation with Theophrast’s Characters : philosopher more than naturalist.